GENETIC INSIGHTS INTO APPLE SCAB (VENTURIA INAEQUALIS (COOKE) G. WINTER) RESISTANCE IN TRADITIONAL APPLE GERMPLASM OF BOSNIA AND HERZEGOVINA: A GENOME-WIDE ASSOCIATION STUDY (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
A genome-wide association study on resistance to the phytopathogenic fungus V. inaequalis was conducted on traditional Bosnian-Herzegovinian apple cultivars. Since the software for conducting GWAS, PLINK ver. 1.9, is adapted to work with diploids, it was necessary to identify and remove triploid varieties beforehand. Triploid identification was performed using axiomFP.py ver. 1.2 software, revealing that 20% of the examined collection were triploids. Based on the ploidy analysis, leaf samples from 35 diploid varieties were collected from the ex situ collection in Goražde (Bosnia and Herzegovina) for further research. The disease intensity was then determined by classifying the leaves into six categories (1-6) using the SAD. By calculating McKinney’s disease index, a variation was observed, ranging from 27.2% (’Senabija’) to 61.1% (’Crvenka’), indicating differences in variety resistance. After isolating and reisolating the pathogen and examining its morphological characteristics, V. inaequalis was identified, and its presence in the mentioned orchard was confirmed. GWAS revealed strong signals on chromosomes 04, 05, and 16 for resistance to this pathogen, using high- resolution SNP markers. This study offers insights into the genetic basis of resistance in traditional apple germplasm from Bosnia and Herzegovina to the phytopathogenic fungus V. inaequalis, the causal agent of apple scab, highlighting the need for further research to develop varieties that are more resistant to this pathogen.